2019
DOI: 10.12681/jode.18964
|View full text |Cite
|
Sign up to set email alerts
|

Teaching mathematical concepts using web-based collaborative enviroments. An eTwinning case study

Abstract: eTwinning is an innovative European program that strengthens lifelong learning and the main purpose of which is the networking of schools with the help of new technologies. It is an initiative of the European Commission to strengthen the collaborative distance learning and the implementation of new innovative instructional methods. Through literature review, this article explores the contribution of the eTwinning project to the cultivation of basic skills, which the European Parliament identifies as keys to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…It was also observed that the curriculum limited the projects. The inconsistencies between eTwinning projects and the curriculum have also been emphasized in the literature (Akdemir, 2017;Αλεξίου, 2019;Crişan, 2013). Consistent with the findings obtained in this study, Camilleri (2016) stated that teachers avoid participating in eTwinning projects because they are not part of the curriculum.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It was also observed that the curriculum limited the projects. The inconsistencies between eTwinning projects and the curriculum have also been emphasized in the literature (Akdemir, 2017;Αλεξίου, 2019;Crişan, 2013). Consistent with the findings obtained in this study, Camilleri (2016) stated that teachers avoid participating in eTwinning projects because they are not part of the curriculum.…”
Section: Resultssupporting
confidence: 88%
“…Ayrıca müfredatın projeleri sınırlandırdığı söylenebilir. Literatürde de yapılan araştırmalarda eTwinning projeleri ile müfredat arasındaki tutarsızlıklar vurgulanmıştır (Akdemir, 2017;Αλεξίου, 2019;Camilleri, 2016;Crişan, 2013). Araştırma sonuçlarına göre okul yöneticilerinin eTwinning proje uygulamalarını desteklemeleri, proje çalışmalarının okullarda yaygınlaştırılması, velilerin projelerin yararları konusunda bilgilendirilmesi, öğretmenlerin bu konudaki çalışmalarının takdir edilmesi ve eTwinning projesi yazan öğretmenler için egzersiz açılıp bu şekilde projelere gereken zamanın sağlanması önerilebilir.…”
Section: Genişletilmiş Türkçe öZetunclassified